Building Loyalty in Punti Kayu Palembang: Tourist Satisfaction Mediating Perceived Value, Safety, and Destination Image - Septian Salim; Xiaoyan Zhang; Yaqubov Abdullojon (Riviera Publishing, 2024)
Tourist loyalty is a crucial factor in ecotourism destinations because it can accommodate the number of tourists visiting Punti Kayu. This study aims to examine how tourist satisfaction can mediate ecotourism destination loyalty through perceived value, perceived safety, and destination image. There are 175 samples in this research, consisting of people who live in Palembang City and have gone to Punti Kayu at least once. Multiple regression analysis is used to analyze the data collected. The Sobel test is conducted as the path analysis to know the mediation effect. The results showed that perceived value, perceived safety, and destination image positively impact tourist satisfaction. Besides that, perceived value, destination image, and tourist satisfaction also positively influence destination loyalty, but perceived safety does not impact ecotourism destination loyalty. In the Sobel test, tourist satisfaction mediates the impact of perceived value, safety, and destination image toward tourist loyalty. The implications of this study highlight the importance of understanding and managing the factors that influence tourist loyalty in ecotourism destinations such as Punti Kayu. By knowing that traveler satisfaction mediates the relationship between perceived value, safety, and destination image with loyalty, destination managers and policy makers can design more effective strategies in improving visitor experience and promoting ecotourism sustainability. Thus, this study not only provides new insights into ecotourism destination management, but also provides a solid foundation for the development of better policies and marketing strategies in the future.